Effectiveness of Lateral Bone Augmentation on the Alveolar Crest Dimension: A Systematic Review and Meta-analysis - Sanz-Sánchez, I; Ortiz-Vigón, A; Sanz-Martín, I; Figuero, E; Sanz, M (Journal of dental research, 2015)
Lateral ridge augmentation procedures are aimed to reconstruct deficient alveolar ridges or to build up peri-implant dehiscence and fenestrations. The objective of this systematic review was to assess the efficacy of these interventions by analyzing data from 40 clinical studies evaluating bone augmentation through either the staged or the simultaneous approach. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) guideline for systematic reviews was used. The primary outcomes were the changes at reentry, in the ridge width, and in the vertical and horizontal dimensions of the peri-implant defect, measured in millimeters, in the staged and simultaneous approaches, respectively. The results of the meta-analysis showed, for the simultaneous approach, a statistically significant defect height reduction when all treatments were analyzed together (weighted mean difference [WMD] = -4.28 mm; 95% confidence interval: [CI] -4.88, -3.69; P < 0.01). The intervention combining bone replacement grafts with barrier membranes was associated with superior outcomes The most frequently used intervention was the combination of xenograft and bioabsorbable membrane. Similarly, for the staged approach, there was a statistically significant horizontal gain when all treatment groups were combined (WMD = 3.90 mm; 95% CI: 3.52, 4.28; P < 0.001). The most frequently used intervention was the use of autogenous bone blocks. Both treatment strategies led to high survival and success rates (>95%) for the implants placed on the regenerated sites. Nonexposed sites gained significantly more in the simultaneous and staged approaches (WMD = 1.1 and 3.1 mm).